2010
DOI: 10.1260/0263-6174.28.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Heavy Metal Ions on Pomegranate (Punica Granatum) Peel: Removal and Recovery of Cr(VI) Ions from a Multi-metal Ion System

Abstract: ABSTRACT:The fruit peel of pomegranate (Punica granatum) exhibits a high affinity for Cu(II), Ni(II), Cd(II) and Zn(II) ions. The maximum adsorption observed was that of Cu(II) ions, followed by Zn(II), Cd(II), Ni(II) and Cr(VI) ions. The adsorption of Cu(II) ions was dependent on the initial Cu(II) ion concentration, pH, adsorbent dose, temperature and contact time. The adsorption isotherms could be described by the Langmuir and Freundlich equations. Application of the χ 2 -test indicated that both these mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…The pomegranate peel was also tested for Cu(II), Ni(II), Cd(II), Zn(II) and Cr(VI) ions [105]. The maximum adsorption was observed for Cu(II) ions, followed by Zn(II), Cd(II), Ni(II) and Cr(VI)…”
Section: Pomegranate Peelmentioning
confidence: 99%
“…The pomegranate peel was also tested for Cu(II), Ni(II), Cd(II), Zn(II) and Cr(VI) ions [105]. The maximum adsorption was observed for Cu(II) ions, followed by Zn(II), Cd(II), Ni(II) and Cr(VI)…”
Section: Pomegranate Peelmentioning
confidence: 99%
“…Few studies have been reported on the application of PGP for removal of different HMs from water samples. Peels were used as such (untreated) or after modification (chemically or thermally) [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…If the plot does not pass through the origin then it is concluded that chemical reaction or film diffusion controls the rate of adsorption (Rao and Rehman, 2010). In the present case the plot of Bt versus time did not pass through origin (Fig.…”
Section: Reichenberg Modelmentioning
confidence: 50%